Ginseng–Astragalus–oxymatrine injection ameliorates cyclophosphamide-induced immunosuppression in mice and enhances the immune activity of RAW264.7 cells. (28th October 2021) - Li, Yuangeng; Yu, Ping; Fu, Wenwen; Cai, Lijian; Yu, Ying; Feng, Zhiqiang; Wang, Yaozhen; Zhang, Fuyuan; Yu, Xiaofeng; Xu, Huali; Sui, Dayun
Abstract: Ethnopharmacological significance: Ginseng quinquefolium (L.), Astragalus membranaceus, and Sophora flavescens Aiton are popular folk medicines in many Asian countries and regions. These three traditional Chinese herbs and their extracts have been reported to considerably enhance the immune function. G. quinquefolium (L.) is considered the king of herbs in China. Traditionally, G. quinquefolium (L.) is believed to replenish vitality, which is considered as immune enhancement in modern Chinese pharmacy. One of the main uses of Astragalus is immunity enhancement; S. flavescens and oxymatrine obtained from its extract have been used to treat leukopenia. Considering the pharmacological properties of Ginseng, Astragalus, and oxymatrine, we evaluated the immunopotentiation effects of their combination, Ginseng–Astragalus –oxymatrine (GAO), in the present study. Aim of the study: This study aimed to expand the clinical application of GAO and to preliminarily explore its mechanism of action by determining whether GAO injection can enhance immunity in vivo and in vitro . Methods: Overall, 17 major chemical components in GAO were analysed using HPLC and LC-MS. The immunity-enhancing effect of GAO was studied in the cyclophosphamide (CTX)-induced immunosuppressive mouse model and RAW 264.7 cells. Results: Quantitative analysis showed that the potential active components of GAO include at least ginsenosides, astragaloside IV, and oxymatrine. GAO could significantly improve the nonspecific immunity including the indices of the thymus and spleen, number of peripheral blood leukocytes, levels of TNF-α and IL-6, phagocytic function of macrophages, and cytotoxic activity of natural killer (NK) cells. Additionally, GAO enhanced the humoural immunity, characterised by the antibody production ability of B cells, and cellular immunity, characterised by the activity of T cells, in immunosuppressed mouse. Moreover, GAO could enhance the phagocytic and adhesion functions of RAW 264.7 cells, which may be related to the activation of reactive oxygen species and NF-κB signalling pathway. Conclusion: GAO could dramatically ameliorate CTX-induced immunosuppression in mouse and stimulate the immune activity in RAW 264.7 cells possibly by activating the NF-κB signalling pathway. Graphical abstract: Image 1